Future Perspectives on the Relevance of Auditory Markers in Prodromal Parkinson's Disease - De Groote, Evelien; De Keyser, Kim; Santens, Patrick; Talsma, Durk; Bockstael, Annelies; Botteldooren, Dick; De Letter, Miet (Frontiers in Neurology, 2020)
Research on auditory processing in Parkinson’s disease (PD) has recently made substantial progress. At present, evidence has been found for altered auditory processing in the clinical stage of PD. The auditory alterations in PD have been demonstrated with low-cost and non-invasive assessments that are already used in routine clinical practice. Since auditory alterations have been reported early in disease progression, it would be highly relevant to investigate whether auditory markers could be provided in the prodromal stage of PD. In addition, auditory alterations in early stage PD might be modulated by dopaminergic medication. Therefore, the aim of this review is (1) to summarize the literature on auditory processing in PD with a specific focus on the early disease stages, (2) to give future perspectives on which audiological and electrophysiological measurements could be useful in the prodromal stage of PD and (3) to assess the effect of dopaminergic medication on potential auditory markers in the prodromal stage of PD.